Conclusion: transitioning from unsustainable to sustainable solutions - Ozturen, Ali; Ozgit, Hale (Emerald Group Publishing Ltd, 2022)
Purpose - This theme issue aims to persuade practitioners and academics of the need to collaborate in support of sustainable development and to identify and implement solutions that enable sustainable tourism development in North Cyprus. The strategic question underlying this theme issue is as follows: transitioning from unsustainable to sustainable: what are the solutions for tourism industry stakeholders in North Cyprus? Design/methodology/approach - The key outcomes of this issue as they relate to the strategic question are reviewed, with particular reference to the contributions made to knowledge, policy and practice as well as the implications for future applied research concerning sustainable tourism development in North Cyprus and Small Island Developing States (SIDS) in general. Findings - Arising from the analysis and synthesis of recommendations, the following themes were proposed as critical concentration points for transitioning from unsustainable to sustainable in the North Cyprus tourism industry: the importance of sustainable tourism indicators (STIs), sustainable development through good governance, engaging cooperatives in urban areas for sustainable development, cultural heritage as a driving force for sustainable development, transportation as a tool for accessible and sustainable tourism, contemporary trends in technology for sustainable development and other factors that could facilitate sustainable tourism development. Originality/value - This article provides a narrative analysis of the findings and makes recommendations for consideration by politicians and tourist industry executives. The solutions include advancing sustainable tourism practices through technology and increasing policymakers' and tourism stakeholders' consciousness. This paper and the collection of articles on which it is based are the first to examine various academic and practitioner approaches to solutions that would help to address the challenges arising and then facilitate sustainable tourism in North Cyprus.
Keywords: Sustainable tourism development; North Cyprus; Planning and policy; Sustainable solutions; Stakeholders